Utilization of Tiktok Videos in Improving Students pronunciation Ability in Senior High School - Nardayana, I Nyoman Agus; Liando, Nihta V. F; Rorimpandey, Rinny (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This research has the purpose of improving students English pronunciation of homograph words by using TikTok videos of native speakers as the media This research is in the form of quantitative which designate the result in the form of numbers tables and charts not in the form of word The data of this research comes from SMA Swadharma Werdhi Agung as the population while focusing on the students of Class XI IPA 1 which consist of 25 students as the sampling of the research In administering this research the researcher used pre test and post test design to find out the improvement of students pronunciation of homograph words by using TikTok videos of native speakers as the media Pre test and post test design is considered as the most suitable for this research which aims to find out improvements from students The result of the study explains that the students pronunciation of homograph words before and after learning using the TikTok videos differs significantly Students ability to pronounce homograph words is positively impacted by TikTok as seen by the post test findings Sig 2 tailed 0 001 lt; 0 05 was the result of the obtained Paired Samples t test This indicates that Ha is accepted while Ho is denied TikTok has a significant impact on students ability to pronounce homograph words as evidenced by the difference between the pre test and post test < p>